Wild weather. Tornadoes! - Hopping, Lorraine Jean.; Wheeler, Jody (New York : Scholastic, 1994)
Describes the work of two people who study tornadoes in the Midwest by discovering and following them.
"Cartwheel Books."
3.5
K-3
Keywords: Tornadoes -- Middle West -- Juvenile literature; Tornadoes; Tornadoes